Kajian Pendahuluan Temuan Struktur Bata di Sambimaya, Indramayu - Nanang Saptono; Endang Widyastuti; Pandu Radea (Balai Arkeologi Provinsi Sulawesi Utara, 2020)
Brick has been used for buildings for a long time. In the area of Sambimaya Village,Juntinyuat District, Indramayu, a brick structure has been found. Based on these findings, apreliminary study is needed for identification. The problem discussed is regarding the typeof building, function, and timeframe. The brick structure in Sambimaya is located in severaldunes which are located in a southwest-northeastern line. The technique of laying bricks ina stack without using an adhesive layer. Through the method of comparison with otherobjects that have been found, it was concluded that the brick structure in Sambimaya was aformer profane building dating from the early days of the spread of Islam in Indramayuaround the 13th - 14th century AD.